Setting international standards for patient and parent involvement and engagement in childhood, adolescent and young adult cancer research: A report from a European Collaborative Workshop. Issue 6 (12th August 2021) - Polanco, Angela; Al‐Saadi, Reem; Tugnait, Suzanne; Scobie, Nicole; Pritchard‐Jones, Kathy
Abstract: Background: Patient and Public Involvement and Engagement (PPIE) in research, advocates for research conducted 'with' not 'for' the affected population. In paediatric oncology research, the parents of children, adolescents and young adults affected by cancer are represented by the term 'public' in the acronym PPIE. Patients (those with cancer and cancer survivors) are also passionate advocates who drive forward the research priorities of children, adolescents and young adults throughout the entire research process. Aims: A workshop was held at an international professional meeting in 2019 with the aim to define Patient and Parent Involvement and Engagement (PPIE); capture PPIE activities on a European level; and to explore the role of PPIE in non‐interventional research. A proposed framework for a European PPIE strategy for childhood, adolescent and young adult cancers was also discussed. Methods: The 60‐minute workshop was attended by health care professionals, researchers, scientists, parents, survivors and charity/support organisations. A presentation to define PPIE, including the difference in terminology for PPIE in the context of childhood, adolescent, and young adult cancers was discussed. Best practice examples from the United Kingdom (UK) helped to demonstrate the positive impact of PPIE in paediatric oncology research. Three breakout groups then explored themes relating to PPIE, namely PPIE priorities, PPIE mapping for Europe, and PPIE in non‐interventional research and data‐linkage. Results: Disparity in PPIE activities across Europe was evident, with ambiguity surrounding terminology and expected roles for PPIE representatives in paediatric oncology research. A lack of PPIE activity in Eastern Europe correlated with a lack of availability for clinical trials and poorer survival rates for paediatric oncology patients. There was unanimous support for PPIE embedded research in all areas, including in non‐interventional studies. Conclusion: A European‐level definition of PPIE for paediatric oncology research is needed. Further exploration into the role and responsibilities of patients, parents, and professionals when undertaking PPIE related activities is also recommended. Best practice examples from the UK, France, Germany, The Netherlands and Belgium demonstrated a preliminary evidence base from which a European PPIE strategy framework can be designed, inclusive of the patient and parent voice.